2015
DOI: 10.1016/j.compositesa.2014.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of discontinuous carbon fibre composites: Damage initiation captured by Digital Image Correlation

Abstract: 10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…[14][15][16][17][18][19] Thus, the observed stress concentration resulted in the appearance of the largest microcrack, which subsequently expanded due to the chain reaction and finally caused specimen's fracture.…”
Section: Optical Microscopy Studiesmentioning
confidence: 97%
“…[14][15][16][17][18][19] Thus, the observed stress concentration resulted in the appearance of the largest microcrack, which subsequently expanded due to the chain reaction and finally caused specimen's fracture.…”
Section: Optical Microscopy Studiesmentioning
confidence: 97%
“…The chips are then sandwiched between two resin sheets, which are subsequently attached together by heating. A different approach, called the directed carbon fiber preform process (DCFP), is also applied in SMC fabrication . Chips are initially deposited onto a region from a revolving chopper head along a series of linear paths.…”
Section: Introductionmentioning
confidence: 99%
“…Wan et al conducted a fractographic analysis of UT‐CTT, and the result indicates that the obtained elastic modulus is almost independent of both the tape length and molding pressure, while the tensile and compressive strength exhibits high molding pressure sensitivity. Johanson et al found significant variation in the strain field between two surfaces of DCFP composites during tension after detailed comparison of strain field taken immediately prior to failure. However, further mechanical analysis is needed to describe the specific effects of microstructural variations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is of particular interest for automotive components, which are typically driven by stiffness rather than strength. The addition of the UD plies will significantly improve the tensile stiffness, but improvements in tensile strength are limited due to stress concentrations in the ASMC [10]. The UD fibres are more effective in bending however, as they are typically located at the surface of the plaque and therefore further from the neutral axis.…”
Section: Introductionmentioning
confidence: 99%